Evaluation of Gait Speed after Applying Kinesio Tape on Quadriceps Femoris Muscle in Patients with Knee Osteoarthritis - Tani, Klejda; Kola, Irena; Shpata, Vjollca; Dhamaj, Fregen (Open access Macedonian journal of medical sciences, 2018)
BACKGROUND: Knee osteoarthritis is a chronic degenerative disease, known as the most common cause of difficulty walking in older adults and subsequently is associated with slow walking. Functional decline, increased risk of falls and the presence of pain are, in many studies, related to the muscle weakness caused by osteoarthritis especially weakness of the quadriceps muscles. Many studies have shown that the strength of the quadriceps femoris muscle can affect gait, by improving or weakening it. Kinesio Tape is a physiotherapeutic technique, which reduces pain and increases muscular strength by irritating the skin receptors.AIM: This study aimed to verify if the application of Kinesio Tape on quadriceps femoris muscle increases gait speed while decreasing the time needed to accomplish the 10-meter walk test in patients with knee osteoarthritis and also in subjects without knee osteoarthritis.METHOD: In this study, we observed the change of gait speed with the help of the 10-meter walk test before, one day and three days after the application of Kinesio Tape in quadriceps femoris muscle. We compared the results of the time needed to perform the 10-meter walk in two groups. In the first group, the Patients group, participated 102 out-patients with a clinical diagnosis of primary knee osteoarthritis, while in the second group, the Control group, participated 73 subjects with a main excluding criterion a clinical diagnosis of primary knee osteoarthritis.RESULTS: Our results indicated that there was a significant decrease of time needed to perform the 10-meter walk test in both groups three days after application of Kinesio Tape on quadriceps femoris muscle. However, there was not a significant change one day after the application of Kinesio Tape compared before its application in both groups.CONCLUSIONS: Our results indicated that there was a significant decrease in time needed to accomplish the 10-meter walk test. Kinesio Tape is a technique that can be used especially when changing walking stereotypes is a long-term goal of the treatment.